Impact of welfare sanctions on employment entry and exit from labor force: Evidence from German survey data - Katja Hillmann; Ingrid Hohenleitner (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2015)
Similar to numerous other European countries, Germany's unemployment policy went through a paradigm shift in 2005, towards activation policy by tightening their monitoring and sanction regime. With our study, we aim to provide causal evidence for whether an intended positive effect of benefit sanctions on employment entry of welfare recipients has been bought at the expense of an unintended enhanced incentive to leave the labor market. Using a mixed proportional hazard model, we draw causal inference of sanction enforcements on unemployment exit hazards. Based on a novel survey sample covering the first three years after the 'Hartz IV' law came into effect, we provide evidence for a positive impact of sanctions on employment as well as on exit from labor force.
Keywords: J48; J63; J64; J68; I38; 330; unemployment benefit sanctions; unemployed welfare recipients; unemployment duration; transition into employment; transition into non-employment; exit from labor force; mixed proportional hazard estimation